Faktor Risiko Hipertensi, Merokok dan Usia terhadap Kejadian Penyakit Jantung Koroner pada Pasien di RSUD Prof. Dr. W. Z. Johannes Kupang - Ice Johanis; Indriati A. Tedju Hinga; Amelya B. Sir (Media Kesehatan Masyarakat, 2020)
Cardiovascular is a heart disease which is caused by the disturbance of heart function and artery. Survey Sample Regristration System (SRS) 2014 in Indonesia shows that coronary heart disease is the second cause of death after stroke as much as 12.9%. The aim of this research is to know the factors of coronary heart disease survivors in RSUD Prof. Dr. W. Z. Johannes Kupang in 2019. This research using observation with case control study. The participants were taken from RSUD Prof. Dr. W. Z. Johannes Kupang. There are 86 coronary heart disease survivors and 86 who are not. The participants were chosen with systematic random sampling with trusting α=0.05. Each variable was tested by chi-square to know the relationship with coronary heart disease. The result of this research shows that hypertension variable (p=0.000, OR=65.753 and 95% CI=23.066-189.960), smoking (p=0.002, OR=2.835 and 95% CI=1.505-5.341), age (p=0.000, OR=54.379 and 95% CI=15.806-187.083) have relation with the cause of coronary heart disease, while gender variable (p=1.000, OR=1.048 and 95% CI=0.574-5.341) and family history (p=1.000, OR=1.066 and 95% CI=0.529-2.151) don’t have any relation with coronary heart disease. Suggests to the society to live healthy life such as do physical activity, eating vegetable and fruit, not smoking, not drinking alcohol, and do routine checkup.